Identifikasi Fungi Endofit yang Diisolasi dari Tanaman Jambu Monyet (Anacardium occidentale L.) pada Wilayah Kabupaten Banyuasin - Habisukan, Ummi Hiras; Musyalina, Aisyah; Oktiansyah, Rian; Laksono, Pandu Jati (Konservasi Hayati, 2023)
Cashew fruit is a plant that is widely grown in eastern Indonesia, such as in NTB, Bali, NTT, South Sulawesi, and Southeast Sulawesi. The study aimed to identify the endophytic fungi found in cashew trees. The method used in this research was taking samples, namely the roots, root bark, stems, bark and leaves of the cashew plant then making instant PDA media mixed with distilled water and antibiotics with direct planting techniques on PDA in Petri dishes. Furthermore, the purification of endophytic fungi was carried out followed by macroscopic and microscopic observations by observing the types of spores, spore forms, and hyphae. The results of macroscopic and microscopic observations on samples of isolates coded KB.AO1 and D.AO1 were identified as belonging to the genus Fusarium, isolates coded KB.AO2 belonged to the genus Trichoderma, isolates coded A.AO1 belonged to the genus Colletotrichum, and isolate A.AO2 belonged to the genus Acremonium, isolate KB.AO1 belongs to the genus Cladosporium, code KB.AO2 belongs to Aspergillus, isolate code BAO1 belongs to Pythium, isolate code BAO2 belongs to Mucor, and isolate code DAO2 belongs to Nigrospora.